2014
DOI: 10.1097/spc.0000000000000043
|View full text |Cite
|
Sign up to set email alerts
|

Nonsurgical oncological management of cancer pain

Abstract: In advanced cancers, oncological therapies must be considered as anti-pain treatments. Identifying molecular targets that have a role in both pain and cancer is an interesting strategy for future drug development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 78 publications
0
9
0
4
Order By: Relevance
“…10,22,63,71,79,112 Conversely, spontaneous pain (without specific eliciting stimuli) and evoked pain (ie, in response to standing, weight-bearing, movement, touch, or other stimuli) associated with CIBP are difficult to treat from the onset because of their intermittent nature, which tends to be very rapid in onset, intense, and of short duration. 10,22,63,71,79,112 Terminology commonly used in the clinical setting to describe evoked or spontaneous pain include breakthrough pain, incident pain, or a pain flare; however, definitions for these terms often lack precision and may overlap. For example, breakthrough pain is defined as a transitory flare of pain in the setting of chronic pain managed with opioid drugs, 127 yet the evoked pain seen in CIBP can occur during weight-bearing without current opioid use.…”
Section: Resultsmentioning
confidence: 99%
“…10,22,63,71,79,112 Conversely, spontaneous pain (without specific eliciting stimuli) and evoked pain (ie, in response to standing, weight-bearing, movement, touch, or other stimuli) associated with CIBP are difficult to treat from the onset because of their intermittent nature, which tends to be very rapid in onset, intense, and of short duration. 10,22,63,71,79,112 Terminology commonly used in the clinical setting to describe evoked or spontaneous pain include breakthrough pain, incident pain, or a pain flare; however, definitions for these terms often lack precision and may overlap. For example, breakthrough pain is defined as a transitory flare of pain in the setting of chronic pain managed with opioid drugs, 127 yet the evoked pain seen in CIBP can occur during weight-bearing without current opioid use.…”
Section: Resultsmentioning
confidence: 99%
“…[46] However, various phase II and III trials found increased cardiovascular events from COX-2 inhibition, thereby tempering the enthusiasm for use of COX-2 inhibitors in cancer patients. [47, 48]…”
Section: 4 Therapeutic Management Of Cibpmentioning
confidence: 99%
“…They act on opioid G-protein coupled receptors (μ, κ, and δ), inhibiting substance P release in the dorsal horn. [47] Opiods are used by nearly 80% of cancer patients for pain control. Sustained and on-demand formulations are used in conjuction to provide pain suppression and breakthrough pain relief respectively.…”
Section: 4 Therapeutic Management Of Cibpmentioning
confidence: 99%
“…Most cancer patients experience pain at some point during the course of their disease and approximately 25% die in pain . The prevalence of cancer pain has been reported to be approximately 60–85%, and is the most commonly reported symptom in cancer patients . One survey of more than 5000 adult cancer patients across multiple countries reported a pain prevalence of 84%, with 94% of those experiencing pain classifying it as moderate to severe and 43% classifying their pain as severe .…”
Section: Introductionmentioning
confidence: 99%